The use of the Rasch model in grading a reference test in mathematics for the fifth grade - أسعد, رجاء; منذر بوبو (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to use the Itme response theory (Rasch model) in constructing a referenced achievement test for the first unit in mathematics for the fifth grade. To achieve this, the descriptive approach was adopted and a set of test items (25 items) were prepared that measure achievement in mathematics in the cognitive domain of the multiple choice type. The research sample consisted of (100) male and female students who were selected by simple random method. The psychometric properties of the achievement test were verified as a tool for the research, and the results showed that the values ​​of the vocabulary difficulty coefficients ranged between (-1.46) and (1.44), and the individual abilities values ​​ranged between (1.32) and (4.70). The results also showed that the paragraphs matched the one-parameter model. In light of the results, a set of recommendations were proposed.